Severe Pulmonary Hypertension Due to Adult-Onset Still's Disease - Ankur Sinha MBBS; Ravikaran Patti MBBS; Paurush Ambesh MBBS; Chukwudi Obiagwu MD; Namrita Malhan BDS; Kabu Chawla MD (SAGE Publishing, 2018)
A 29-year-old female with adult-onset Still's disease (AOSD) presented with progressive shortness of breath both on rest and on exertion, increased abdominal girth, and swelling in both legs. She was on oral prednisone and was recently started on canakinumab (interleukin-1 antagonist) for joint pain and rash of AOSD. Echocardiogram showed severely dilated right ventricle, dilated pulmonary artery, moderately reduced right ventricular systolic function, but with normal left ventricular systolic function. Computed tomography with contrast ruled out pulmonary embolism. Blood tests ruled out other rheumatologic diseases. The patient was diagnosed with right-sided heart failure likely secondary to AOSD. Right heart catheterization was needed but could not be performed because of severely dilated pulmonary artery. The patient was transferred to a higher center for further management and possible cardiopulmonary transplant.